Efektivitas Scientific Approach terhadap Materi PAI pada Merdeka Belajar - Miftakhul Rohman; Asyharul Muttaqin (SINDA: Comprehensive Journal of Islamic Social Studies, 2022)
The research discusses the scientific approach used in learning Islamic Religious Education and Character Education in the Independent Learning Curriculum in terms of the positivistic scientific paradigm initiated by Auguste Comte. The results of this study state that the scientific approach in learning the Merdeka curriculum is learning through the steps of the scientific method. This scientific approach is very relevant and appropriate if it is used in developing an independent learning curriculum using a positivistic paradigm. However, there are some points that are less relevant in learning Islamic Religious Education and Morals such as faith and monotheism. Therefore, this scientific approach is only applied to fiqh, morals, al-quran hadith, Islamic cultural history, so the scientific approach (scientific approach) is very appropriate to be applied to the learning process. The form of activity is in the form of a project. What students must complete.